Pengaruh Disiplin Belajar Pada Masa Pandemi Covid-19 Terhadap Hasil Belajar Siswa Kelas Tinggi SDN 16 Sungai Limau Kabupaten Padang Pariaman - Roza, Riza Elvira; Syari, Elsy Melia (Jurnal Pendidikan Nasional, 2021)
ABSTRACT This research is motivated by the low learning outcomes of high grade students at SDN 16 Sungai Limau. This problem is marked by the fact that there are still many students who are less disciplined towards online and offline learning. The purpose of this study was to determine the effect of learning discipline during the covid-19 pandemic on the learning outcomes of highclass students at SDN 16 Sungai Limau, Padang Pariaman Regency. This research is a correlational study. The population in this study amounted to 50 students and the entire population was sampled with a total sampling technique. The instrument used was a closed questionnaire to measure student learning discipline variables to describe student learning outcomes for high grade students at SDN 16 Sungai Limau. The data analysis technique used is descriptive statistical analysis and inferential statistics. The results showed that there was an influence of learning discipline on the learning outcomes of high grade students at SDN 16 Sungai Limau. This is indicated by the correlation coefficient value of 0.799, thus indicating that the learning discipline variable has an influence on student learning outcomes (t count 9.215 > t table 1.678). While the value of the determinant coefficient is 63.84%, this shows that the learning outcomes of high grade students at SDN 16 Sungai Limau 63.84% are influenced by student discipline variables, while the remaining 36.16% is influenced by other variables.